Clinical simulations in pharmacology I - Williams & Wilkins (Baltimore, MD : Williams & Wilkins, 1998)
(Producer) Provides patient case studies enhanced by the power of multimedia. Includes four units: Adolescent with asthma; Diabetic outpatient clinic; Pharmacotherapeutics for gastrointestinal pain; and Pharmacological treatment for depression.
Title from disc label.
'Includes Stedman's electronic medical dictionary'--Container.
CD-ROM is available at Makmal Multimedia, Perpustakaan Perubatan.
System requirements: IBM-PC or compatible computer, 486 66MHz or faster CPU; 8 MB RAM, 3 MB free disk space; Windows 3.1, Windows 3.11, and Windows 95 to the extent that Macromedia Director and Authorware are compatible with Windows 95; SVGA display supporting at least 256 colors; double speed CD-ROM; Windows compatible sd. card.
Keywords: Drug Therapy -- nursing